Studi Pemikiran Abdullah Ahmed An-Naim tentang Hukum Pidana Islan dan HAM - Sulthon, M (Al-Jinayah : Jurnal Hukum Pidana Islam, 2021)
The preliminary finding of this research acourding An-Naim is the contradiction between Islamic law and human rights caused by philosophy and tendancy of law. Islamic law is based on revelation, meanwhile the human rights on human experience. Islamic law emphasizes to the collective protection aspect, but the human rights concern to oneself interest. Islamic Criminal Law is not only to protrude its sanction aspect, but also to see the positive’s that’s social benefit..The above research found to respond the main problem of law Islamic criminal according An-Naim to the perspective of human rights. Sanction of dead punishment has been applied in Indonesia law sanction, while punishmen sanction of hand cutting and beating is not yet applied. On the other hand, the movement of human rights becomes stronger to refuse the implementation of islamic law sanction which is suppoused not relevance with the standard of human rights.This research position towards the anothers to strengthen the previous research, especially to strengthen the writing found ‘Topo Santoso’ that shows the priority of Islamic criminal law sanction.This research makes up normative and sociology’s. The analysis technique performed as descriptive analysis with the method : doctrine-comparative, analytic-deductive normative and analytic-inductive normative. Hence, the summary of this result study is withdrawn as deductive and inductive based on the data.